TonEBP/NFAT5 promotes obesity and insulin resistance by epigenetic suppression of white adipose tissue beiging - Hwan Hee Lee (Nature Portfolio, 2019)
Activation of thermogenic beige adipocytes within white adipose tissue increases energy expenditure. Here, the authors show that expression of TonEBP in adipocytes is increased when mice are fed a high fat diet and that it suppresses expression of beta3-adrenoreceptor.